(untitled) (Вестник КазНУ. Серия Востоковедения, 2018)
This article is devoted to the actual problem of demographic policy and the demographic situation in China. The author analyzes the consequences of the policy of birth control in the PRC and new approaches to regulating the demographic policy and socio-economic tasks related to the demographic situation of modern China, voiced at the XIX Congress of the CPC